Effects of preparation methods on potato microstructure and digestibility: An in vitro study. (15th November 2016) - Tian, Jinhu; Chen, Shiguo; Wu, Chunhua; Chen, Jingqiu; Du, Xinyi; Chen, Jianchu; Liu, Donghong; Ye, Xingqian
Highlights: Preparation methods on potato microstructure and digestion were evaluated. Apparent morphology differences were observed after boiling, cooling and reheating. The relative crystallinity of cooled was higher than reheated and boiled. Cooling and reheating significantly affected the digestibility of potato. Abstract: The effects of preparation method (boiled, cooled, and reheated) on the structural characteristics and in vitro digestibility of potato were investigated. The highest equilibrium starch hydrolysis was obtained after boiling (82.21%), followed by reheating (66.98%) and cooling (54.31%). The potato after cooling treatment exhibited a narrower melting temperature range and a higher melting enthalpy compared with the potatoes after boiling and the microwave reheating. X-ray diffraction patterns revealed that the relative crystallinity of the cooled potato was higher than those of the reheated and boiled potatoes, consistent with the results in melting enthalpy. Moreover, compared with the boiled potato, a large number of wrinkles were observed on the surface of the cooled potato, whereas after microwave reheating, larger clearances of starch granule regions were found. This study demonstrated that cooling and microwave reheating significantly affected the potato's microstructure and digestibility and were suggested as alternative choices to prepare potato dishes.